Difference Between Prevalence of Urinary Tract Infection Before and After DJ Stent Insertion in Pelvic Tumor Patients - Daryanto, Besut; Ardiani, Astarin (International Journal of Psychosocial Rehabilitation, 2020)
This research aimed to found out different prevalence of urinary tract infection in pelvic tumor patient before DJ Stent insertion and on the 1st, 2nd and 3rd months after DJ stent insertion. This is a prospective cohort study, between Mei to October 2017, a total of 42 women, diagnosed with pelvic tumor and hydronephrosis, never used DJ stent before, sterile urine culture with bacterial count of < 105 CFU before DJ stent insertion, and inserted DJ stent in either one or both side. All underwent urine culture and antibiotic sensitivity test before DJ stent insertion and after DJ stent insertion every consecutive month for three months. Mean age was (46,7±11,1), cervix cancer account 54,76% of all pelvic tumor, with 52,4% of DJ stent were placed on both side. Significant different in urinary tract infection was found in before and one month after DJ stent insertion (p = 0.00). Meanwhile, no significant different seen in urinary tract infection prevalence between 1st ,2nd and 3rd months after DJ stent insertion (p > 0.05). E.coli account (17(41%)) of all bacterial growth, with ciprofloxacin (14) as the most sensitive antibiotics among all bacteria. urinary tract infection is significant after DJ stent was inserted, while there was no significant difference in urinary tract infection prevalence between period of 1, 2 and 3 months after DJ stent insertion. E.coli is the most common bacterial growth and Ciprofloxacin is the most sensitive antibiotic.